Q4: Simplifying 3^2x3^9:
Using the property that states a^m * a^n = a^(m+n), we can add the exponents.
3^2x3^9 = 3^(2+9)
= 3^11
Q5: Simplifying (-3)^-5(-3)^4:
Using the property that states (a^m)^n = a^(m*n), we can simplify the expression.
(-3)^-5(-3)^4 = (-3)^(-5*4)
= (-3)^(-20)
Q6: Simplifying (z^3)^4:
Using the property that states (a^m)^n = a^(m*n), we can simplify the expression.
(z^3)^4 = z^(3*4)
= z^12
Show all your work
Q4: Simplify and write your answer in exponential form
3^2x3^9
Q5: Simplify the expression.
(- 3)^-5(- 3)^4
Q6: Simplify
(z^3)^4
1 answer